A case with cardiac, skeletal, speech, and motor traits narrows the subtelomeric 19p13.3 microdeletion region to 46 kb. Issue 1 (22nd October 2022) - Peter, Beate
Abstract: Subtelomeric 19p13.3 deletions have been associated with diverse anatomical and developmental phenotypes. A recent study of eight patients with subtelomeric interstitial 19p13.3 microdeletions at 0.3–1.4 Mb (hg 19) showed associations with growth restrictions, skeletal deformities, craniofacial anomalies, congenital heart defects, renal malformations, hernias, immune system deficits, fine and gross motor delays, speech delays, and developmental and learning delays. The authors defined two small regions of overlap containing four and 11 genes, respectively, with potential haploinsufficiency. Here, we present a new case with a de novo 184 kb deletion containing eight genes, three of which fall into the second previously identified small region of overlap, reducing the shared region to 46 kb. Phenotypic traits include most of the core findings in the previously reported cases but not growth restrictions, craniofacial anomalies, renal malformation, and learning disability. A closer look at the speech and motor delays reveals apraxic speech and discoordination in the fine and gross motor domain, consistent with cerebellar involvement across motor systems. Findings are consistent with a role of AZU1 in the observed immune deficiencies and PTBP1 in the observed skeletal, abdominal, speech, language, motor, and sensory traits. This case thus contributes to a more nuanced understanding of the subtelomeric 19p13.3 deletion region.